Persistent and toxic substances in the Venice lagoon biota : an approach for quantitative data analysis for risk management - MINIERO, Roberto; CERETTI, Giuseppe; INGELIDO, Anna Maria; VIO, Piero; DI DOMENICO, Alessandro; CHERIN, Evelina; DELLATTE, Elena; DE LUCA, Silvia; FERRI, Fabiola; FOCHI, Igor; FULGENZI, Anna Rita; GRIM, Federico; et al. (Annali dell'Istituto superiore di sanita, 2006)
An approach based on hypothesis testing for the management of persistent inorganic and organic toxic chemicals (PTS/POPs) detected in clams and mussels from the Venice lagoon is presented. The chemicals of interest for this evaluation were the polychlorinated biphenyls (PCBs), dibenzodioxins (PCDDs), and dibenzofurans (PCDFs), hexachlorobenzene (HCB), and the heavy metals cadmium (Cd), mercury (Hg), and lead (Pb). Two statistically different populations of data for PCDDs+PCDFs (TEQs), HCB, Cd, and Pb, associated with biota samples collected respectively in the lagoon central district and in the southern and northern districts were identified. The central district is under the impact of the Porto Marghera industrial settlement and the city of Venice, whereas the southern and northern districts are subject to a general impact. Of the aforementioned chemicals, those with more discriminating power were found to be HCB and PCDDs+PCDFs.